Outcome of infants with hydrocephalus findings on Intra-Uterine Ultrasound (USG) examination at Dr. Soetomo Hospital, Surabaya, Indonesia, in 2015-2017 - Lourin Nova; Mohammad Aldika Akbar; Agus Sulistyono; Wihasto Suryaningtyas; Prastiya Indra Gunawan (Universitas Airlangga, 2019)
Objectives: to report the outcome of cases with hydrocephalus findings on intra-uterine ultrasound (USG) examinations which happened between January 2015 - December 2017 at Dr. Soetomo Hospital.Case Report: During the period of January 2015 - December 2017, 20 pregnant women were found who performed an ante natal examination and obtained the fetus with hydrocephalus on intra uterine ultrasound examination. At the time of delivery, out of a total of 20 cases, all babies were born alive, but only 12 babies performed shunting operations with VP Shunt. But at the time of follow up the condition of the baby when the search of this case, found only 7 cases with living conditions. This is probably due to non-routine post-action control to ensure shunt conditions and complications that can result from shunt or other conditions. As seen from the growth and development of 7 surviving children, all cases with normal growth conditions were established based on WHO growth curve and developmental obstacles in all cases with evaluation using DDST II.Conclusion: Ultrasound examination is useful for determining the fetal prognosis, but for fetoscopic examination and intra uterine operative action remains controversial. Similarly, to determine the exact termination time and delivery mode. Pre-natal counseling and examination is required in mothers with a history of fetal hydrocephalus in previous pregnancies. With routine control is expected better outcomes in fetal hydrocephalus.